2010
DOI: 10.1021/ie100770e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Methyl Isobutyl Ketone over Pd/MgO/SiO2

Abstract: In this paper, we have examined the activity and selectivity of catalysts for the one-step, gas phase production of methyl isobutyl ketone (MIBK) from acetone (propanone) over the temperature range 373-573 K. The catalysts used were an impregnated MgO/silica, a Pd-MgO/silica formed from coimpregnation of the nitrates, and a Pd supported on a 1% Mg doped silica, Pd/Mg-SiO 2 . Using MgO/silica, mesityl oxide (MO) was formed with 100% selectivity at 373 and 473 K. Addition of Pd gave 100% selectivity to MIBK at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…[36] also proposed the same reaction route during the synthesis of methyl isobutyl ketone (MIK) over Pd/MgO/SiO 2 . On the other hand, MO was not detected in our work, which can be explained by the fact that the reaction from MO to MIK is spontaneous (enthalpy: ∆H 400 K (kcal/mol) = −14.5; Gibbs free energy: ∆G 400 K (kcal/mol) = −12.1) [36,37]. Here, it can thus be speculated that the formation of BTXM can be caused by a further aldol condensation between mesityl oxide (MO) and acetone, followed by dehydration, hydrogenation, and isomerization.…”
Section: Effect Of Temperature and Pressurecontrasting
confidence: 74%
“…[36] also proposed the same reaction route during the synthesis of methyl isobutyl ketone (MIK) over Pd/MgO/SiO 2 . On the other hand, MO was not detected in our work, which can be explained by the fact that the reaction from MO to MIK is spontaneous (enthalpy: ∆H 400 K (kcal/mol) = −14.5; Gibbs free energy: ∆G 400 K (kcal/mol) = −12.1) [36,37]. Here, it can thus be speculated that the formation of BTXM can be caused by a further aldol condensation between mesityl oxide (MO) and acetone, followed by dehydration, hydrogenation, and isomerization.…”
Section: Effect Of Temperature and Pressurecontrasting
confidence: 74%
“…MIK is considered a crucial product at low temperature. Similarly, Gamman et al [ 34 ] reported an aldol condensation reaction pathway of acetone to form MIK over Pd/MgO/SiO 2 catalysts. Reaction (6) is the mainly hydrogenated reaction to form propane.…”
Section: Proposed Reaction Pathways Of Acetone Hdomentioning
confidence: 99%
“…For example, mesitylene can be formed through that route. [ 34,39 ] In addition, other alkylbenzenes were probably produced via further isomerization and deoxygenation reaction of intermediates (C 6 ‐C 9 ketones). Reaction (7) illustrated a reversible reaction between acetone and acetic acid.…”
Section: Proposed Reaction Pathways Of Acetone Hdomentioning
confidence: 99%
“…Many different supports have been applied as catalysts for the two first steps in the MIBK production, whereas the preferred metals chosen for the hydrogenation step have been noble metals, such as Pd, [2][3][4][5][6][7][8][9][10][11][12][13][14] Pt, [9,[15][16][17] and Rh. [18] Noble metals are known to be efficient in hydrogenation reactions, however, their high cost has stimulated the search for cheaper alternatives, such as Ni [9,19,20] and Cu.…”
Section: Introductionmentioning
confidence: 99%